The evolution of public transport contracts in France - Odile Heddebaut (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2017)
This paper presents the evolution of public transport contracts in France and the historical and legal contexts which led to their reorganisation. We first examine the evolution of the territorial distribution of institutional powers in transportation mainly for passengers. A focus is made on the regional passenger railway reform in France that allowed the 20 French metropolitan regions to become transport organising authorities following a first experiment by seven volunteer regions. The Nord-Pas de Calais region is taken as an example. Then the urban public transport contracts are analysed focussing on different possibilities of contract and finally, the specific case of transport organisation in the Paris Île de France region is studied.
Keywords: 330; Schienenpersonennahverkehr; Öffentlicher Nahverkehr; Kommunale Verkehrspolitik; Nahverkehrspolitik; Nord-Pas-de-Calais